Quality of life in patients with scabies: A cross‐sectional study using Dermatology Life Quality Index (DLQI) questionnaire - Sushil Paudel; Prajwal Pudasaini; Sadiksha Adhikari; Manish Bhakta Pradhan; K. C. Shekhar Babu (JEADV Clinical Practice, 2023)
Abstract Background Scabies is one of the most common causes of dermatology outpatient visits. Scabies can cause significant impairment in quality of life of patients. Methods All consenting patients with Scabies presenting to the clinic from April 2021 to April 2022 were enrolled in this observational study. Clinical evaluation for scabies, sites involved and patient demographics was recorded. All participants were asked to complete the Nepali Dermatology Life Quality Index (DLQI) questionnaire. Results This study included 119 patients. Of these, 76.5% were males, 61.3% were living single and 57.1% were students. The mean age of the study population was 24.69 ± 8.74 years. Almost half of the patients (42.8%) had had scabies for more than 1 month; a similar number of patients had at least one other member of the family with similar symptoms. The overall impairment in quality of life (QoL) was ‘very large’ with a total DLQI score of 12.91 ± 5.93. Conclusions Scabies exerts a strong impact on the quality of life of patients. Our study showed that almost half of the patients had a disease duration of more than 1 month.